2017
DOI: 10.1111/fcsr.12202
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice: Implications for Cash and Credit Management Behaviors

Abstract: This study explored the relationships between subjective and objective financial knowledge with cash and credit behavior. A nationally representative sample of American consumers over the age of 18 were surveyed online in 2012 about four financial behaviors: (1) maintenance of an emergency account, (2) prompt payment of credit card balances, (3) checking credit reports, and (4) avoiding checking account overdrafts. The results of logistic regressions indicated that higher levels of both objective and subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
3
11
0
1
Order By: Relevance
“…However, in consumer-behavior studies, 20 per cent is deemed high, which makes it difficult to lay down general rules for acceptable R-squared levels. Therefore, the results for the total sample indicate relevance in the sense that they stress that the higher people's actual financial knowledge, in line with the results found in Chen and Volpe (1998), Lusardi and Mitchell (2006, 2007a, 2007b, Hung et al (2009aHung et al ( , 2009b Garber and Koyama (2016) and Allgood and Walstad (2016) and self-confidence, similarly concluded by Robb and Woodyard (2011), Asaad (2015), Allgood and Walstad (2016) and Woodyard et al (2017), the better their financial behavior. Despite these results, the total sample was clearly heterogeneous in terms of people's actual financial knowledge and self-confidence levels, justifying multi-group analyses to investigate any differences for the study's conceptual model.…”
Section: Financial Literacy In Brazilsupporting
confidence: 83%
See 2 more Smart Citations
“…However, in consumer-behavior studies, 20 per cent is deemed high, which makes it difficult to lay down general rules for acceptable R-squared levels. Therefore, the results for the total sample indicate relevance in the sense that they stress that the higher people's actual financial knowledge, in line with the results found in Chen and Volpe (1998), Lusardi and Mitchell (2006, 2007a, 2007b, Hung et al (2009aHung et al ( , 2009b Garber and Koyama (2016) and Allgood and Walstad (2016) and self-confidence, similarly concluded by Robb and Woodyard (2011), Asaad (2015), Allgood and Walstad (2016) and Woodyard et al (2017), the better their financial behavior. Despite these results, the total sample was clearly heterogeneous in terms of people's actual financial knowledge and self-confidence levels, justifying multi-group analyses to investigate any differences for the study's conceptual model.…”
Section: Financial Literacy In Brazilsupporting
confidence: 83%
“…The literature likewise includes studies that investigate relationships involving other levels of self-confidence and actual financial knowledge. Allgood and Walstad (2016) find that self-confidence is a good predictor of financial behavior, which finds confirmation in Woodyard et al (2017), who conclude that both actual and perceived knowledge are positively associated with desirable behaviors. These studies therefore support the final hypotheses to be investigated here:…”
Section: Financial Literacy In Brazilmentioning
confidence: 83%
See 1 more Smart Citation
“…Huston (2010); Hilgert et al (2003) defined financial literacy as financial knowledge, with this also seen as the basis of appropriate financial decision-making (Lusardi, 2012b). Previous studies have shown that financial knowledge affects both financial behavior (Babiarz and Robb, 2014;Woodyard et al, 2017), financial goal (Priyadharshini,2017) and financial decisions (Asaad, 2015;Parker et al, 2012). To measure the level of financial knowledge, subjective financial knowledge or perceived knowledge and objective financial knowledge have been used.…”
Section: Subjective Financial Knowledgementioning
confidence: 99%
“…In several studies related to financial knowledge, concerns about the inconsistency between objective and subjective financial knowledge has gained attention (Kim, Lee, & Hanna, 2019; Porto & Xiao, 2016; Robb, Babiarz, Woodyard, & Seay, 2015). Objective financial knowledge refers to one’s actual knowledge, whereas subjective knowledge refers to the perception of one’s knowledge (Asaad, 2015; Robb et al, 2015; Woodyard, Robb, Babiarz, & Jung, 2017). Individuals are overconfident in financial knowledge when their perception of their knowledge exceeds their understanding of financial matters (Porto & Xiao, 2016; Robb et al, 2015).…”
mentioning
confidence: 99%